A Nonrandomized, Open-Label, Multicenter, Phase 4 Pilot Study on the Effect and Safety of ILUVIEN® in Chronic Diabetic Macular Edema Patients Considered Insufficiently Responsive to Available Therapies (RESPOND) - Figueira, J (2017)
PURPOSE: The aim of this study was to assess the effectiveness and safety of ILUVIEN® in patients with chronic diabetic macular edema (DME) who were insufficiently responsive to prior therapies. METHODS: This is a prospective, nonrandomized, multicenter, open-label, phase 4 pilot study assessing the effectiveness and safety of ILUVIEN® involving 12 patients insufficiently responsive to available therapies. Assessments were performed at screening, baseline, week 1, and months 1, 3, 6, 9, and 12. Demographics, medical/ophthalmic history, prior laser, anti-VEGF, and steroid treatments, and lab tests were recorded at screening. A complete ophthalmic examination and SD-OCT were performed at screening and at all follow-up visits. RESULTS: The patients showed improvements in best-corrected visual acuity (+3.7 letters), with greater improvement among pseudophakic patients (+6.8 letters) compared with phakic patients (-2.5 letters) 12 months after ILUVIEN®. The mean central subfield thickness decrease from baseline to month 12 was statistically significant, with a rapid reduction in the first week. Regarding safety, only 2 patients showed an intraocular pressure (IOP) increase over 25 mm Hg during the study, and the rise in IOP was well managed with eye drops only. CONCLUSIONS: This prospective and pilot study suggests that ILUVIEN® is safe and may be considered effective for chronic DME patients insufficiently responsive to other available therapies as it showed a rapid and sustained improvement of macular edema obtained after treatment with ILUVIEN®.